Review: Indonesian Herbal Ingredients as Immune Booster - Yasmiwar Susilawati; Norisca Aliza Putriana; Silmi Auliya Zakariya (Tropical Biopharmaca Research Center, IPB University, 2022)
The COVID-19 pandemic caused by SARS-CoV-2 virus lead to massive death counts in parts of the world, including in Indonesia. Indonesian people often use herbal medicine as a way to increase their immune system, to prevent infection, and to accelerate the healing process of COVID-19. They are used to compose herbs with several medicinal plants as ingredients. This review was aimed to provide information about immune booster herbs in Indonesia along with how to make it, its composition, its chemical contents, and how to use it in order to obtain scientific basis in understanding the efficacy and the herbal formulation. The method was carried out by browsing the literature from 2011-2021 through Google Scholar database from September 2021 to October 2021. The keywords used were